PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN TOTAL ASSETS TURNOVER (TATO) TERHADAP RETURN ON EQUITY (ROE) PADA PT HEXINDO ADIPERKASA Tbk (PERIODE 2003-2023) - Eka Rachmawati, Renita; Khuzaeni (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER) and Total Assets Turnover (TATO) on Return On Equity (ROE) in PT Hexindo Adiperkasa Tbk (Period 2003-2023). The method in this study is quantitative associative. The data analysis methods used include: Descriptive Statistical Test, Classical Assumption Test (Normality, Multicollinearity, Heteroscedasticity and Autocorrelation), Simple and Multiple Linear Regression Test, T Test (partial) & F Test (simultaneous), Coefficient of Determination Test. The result of this study is that the Current Ratio (CR) does not have a significant effect on Return On Equity (ROE), this is evidenced by the value of Tcount -2.087 < Table 2.10982 with a significant value of 0.051 > 0.05. Debt to Equity Ratio (DER) has no significant effect on Return On Equity (ROE), this is evidenced by the value of 1.009 < 2.10982 with a significant value of 0.326 > 0.05. Total Assets Turnover (TATO) has a significant effect on Return On Equity (ROE), this is evidenced by the value of 4.977 > 2.10982 in Table with a significant value of 0.000 < 0.05. Meanwhile, simultaneous testing, Current Ratio (CR), Debt to Equity Ratio (DER) and Total Assets Turnover (TATO) have a significant effect on Return On Equity (ROE), this is evidenced by the value of Fcal 11.152 > Ftable 3.20 with a significant value of 0.000 < 0.05. The determination coefficient shows an Adjusted R Square value of 0.604 or 60.4%, which indicates that the Current Ratio, Debt to Equity Ratio and Total Assets Turnover affect Return On Equity by 60.4%, with additional factors not covered in this study affecting 39.6%.